Extracellular Vesicle-Mediated Chemoresistance in Oral Squamous Cell Carcinoma - Law, Zhu-Jun (Front Mol Biosci, 2021)
Oral Squamous Cell Carcinoma (OSCC) remains a cancer with poor prognosis and high recurrence rate. Even with multimodal treatment options available for OSCC, tumor drug resistance is still a persistent problem, leading to increased tumor invasiveness among OSCC patients. An emerging trend of thought proposes that extracellular vesicles (EVs) play a role in facilitating tumor progression and chemoresistance via signaling between tumor cells. In particular, exosomes and microvesicles are heavily implicated in this process by various studies. Where primary studies into a particular EV-mediated chemoresistance mechanism in OSCC are limited, similar studies on other cancer cell types will be used in the discussion below to provide ideas for a new line of investigation into OSCC chemoresistance. By understanding how EVs are or may be involved in OSCC chemoresistance, novel targeted therapies such as EV inhibition may be an effective alternative to current treatment options in the near future. In this review, the current understandings on OSCC drug mechanisms under the novel context of exosomes and microvesicles were reviewed, including shuttling of miRNA content, drug efflux, alteration of vesicular pH, anti-apoptotic signaling, modulation of DNA damage repair, immunomodulation, epithelial-to-mesenchymal transition and maintenance of tumor by cancer stem cells.